A novel tumor-activated ALA fusion protein for specific inhibition on the growth and invasion of breast cancer cells MDA-MB-231. (1st January 2017) - Liu, Xiufeng; Liu, Xintong; Sunchen, Suwen; Liu, Meixia; Shen, Chen; Wu, Juanjuan; Zhao, Wanli; Yu, Boyang; Liu, Jihua
Abstract: Objective: The aim of this research was to develop a novel ALA fusion protein for target to the malignant cells surface with high uPAR expression and locally release of the scorpion toxin AGAP in an uPA-cleavable manner. It will provide an effective approach for controlled release of the peptide toxins to treat cancerous cells. Methods: The ALA fusion proteins were expressed in pichia pastoris, and the recombinant proteins were purified by Ni-NTA affinity chromatography. The proteins were added to human breast cancer cells (MDA-MB-231) and human embryonic kidney cells (HEK-293) in order to investigate the characteristic of selective targeting and releasing of scorpion toxin AGAP in cancer cells with high uPAR expression. The inhibitory effect of ALA on MDA-MB-231, MCF7, LO2 and HEK-293 was evaluated by MTT assay. Moreover, the antiproliferation mechanism of ALA was determined by flow cytometric and western blot analysis. Results: The results showed that ALA could target MDA-MB-231 cells and the scorpion toxin AGAP could be released with high efficiency and selectivity. ALA inhibited the growth and invasion of breast cancer cells MDA-MB231. Also, cell apoptosis pathway was found to be associated with the inhibition mechanism of ALA according to the data of flow cytometric and western blot analysis. Therefore, ALA could be a novel antitumor candidate for targeting treatment of malignant cell. Conclusions: This study successfully demonstrated that fusion of biotoxins with tumor target domain could provide a simple yet effective way to delivery of peptide or protein drugs.